A systematic mapping study on tourist-tourist interactions - Li, Jing; Kunasekaran, Puvaneswaran; Chia, Kei Wei; Chuah, Stephanie Hui-Wen
This is the first quantitative systematic literature review to identify cutting-edge studies and research gaps in the field of interactions between tourists. A Systematic Mapping Study (SMS) was used to structure current literature in this broad research field based on the analysis of interactive objects, situations, themes, methodologies, and theoretical underpinnings. In total, 85 published articles between 2011 and 2020 were analyzed. The results indicate that extant research has focused more on tourists' interactions with unfamiliar travelers for helpful information and emotional support, rather than on their social ties and communications with travel companions. Little is understood about the critical factors that lead to positive interactions among tourists and the contributions of tourism providers in this process. At the same time, there is still a lack of research on negative social interactions between tourists that result in value destruction. Furthermore, limited literature exists on the chronological sequence and inner workings of tourists social communications in different situations. Suggestions for future research include widening basic theoretical frameworks and research approaches to provide a more comprehensive view of interactions between tourists.